Pre-polymerization method of solid catalyst component for olefin polymerization and application thereof

By reacting the catalyst component A with contact reaction with alkyl aluminum and the external electron donor compound in an inert solvent, and adding hydrogen during the olefin polymerization process, the problem of insufficient hydrogen regulation sensitivity of the catalyst is solved, and the bulk density and processing performance of the polymer are improved.

CN119798489AActive Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202311309269.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

In industrial applications, existing olefin polymerization catalysts have the problem of insufficient catalyst hydrogen adjustment sensitivity, resulting in a high fine powder content in the polymer.

Method used

In the presence of an inert solvent, catalyst component A, aluminum alkyl and external electron donor compound are contacted, and α-olefin and hydrogen are added to the reaction system to perform a prepolymerization reaction, which changes the composition and structure of the active center, thereby improving the hydrogen adjustment sensitivity of the catalyst.

Benefits of technology

It improves the hydrogen adjustment sensitivity of the catalyst, enhances the bulk density of the polymer, and has a wider product molecular weight distribution, improving processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798489A_ABST
    Figure CN119798489A_ABST
Patent Text Reader

Abstract

The invention provides a prepolymerization method and application of a solid catalyst component for olefin polymerization, and belongs to the technical field of olefin polymerization. The solid catalyst component obtained by the prepolymerization method comprises a magnesium element, a titanium element, halogen, poly-alpha-olefin and an internal electron donor compound, the internal electron donor compound comprises a compound as shown in a formula (I); the magnesium element comes from a magnesium-containing carrier comprising a magnesium compound shown in a formula (II). The catalyst has high hydrogen regulation sensitivity and high bulk density, the molecular weight distribution of the product is wider, and the processability of the product is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of olefin polymerization catalysts, and in particular to a prepolymerization method of a solid catalyst component for olefin polymerization and application thereof. Background Art

[0002] As one of the important components of the five major synthetic resins, polypropylene resin has a wide range of applications in industry and life due to its excellent performance characteristics. Since the discovery of the Ziegler-Natta catalyst in the last century, its production capacity and output have been continuously improved, especially in the past decade or so, and the internal driving force of this rapid development lies in the continuous upgrading of catalyst technology and processing technology. Catalyst technology is the core technology behind this development. The carrier is the cornerstone of the Ziegler-Natta catalyst and determines the morphology and performance of the catalyst.

[0003] Only spherical catalysts can produce spherical polymers with good fluidity. Industrial annular polypropylene process equipment basically uses this type of catalyst. Similarly, only spherical carriers can produce spherical catalysts. For example, CN201610881057.6 discloses a new method for preparing a carrier: using magnesium chloride, alcohol and epoxy compounds to synthesize spherical carriers. However, the spherical catalyst may be broken during the production process of industrial polypropylene and no spherical polymer can be obtained. Therefore, it must first be pre-polymerized to finally obtain a spherical polymer. Moreover, in the production of polypropylene, there is still a phenomenon of polymer particle breakage, resulting in a high content of fine powder in the polymer. Therefore, many companies or research institutions have conducted research on pre-polymerization.

[0004] For example, US9453088B2 discloses a method of prepolymerizing an olefin in contact with a catalyst to obtain a prepolymerized catalyst having an activity multiple less than 50. For example, US7329714B2 discloses a method of prepolymerizing propylene or 4-methyl-1-pentene.

[0005] The purpose of the above-mentioned prepolymerized catalysts is to reduce the breakage phenomenon so as to reduce the content of fine powder in the final polymer. However, there is still the problem of insufficient sensitivity of the catalyst to hydrogen regulation. Summary of the invention

[0006] The purpose of the present invention is to provide a prepolymerization method for a solid catalyst component for olefin polymerization and its application. The solid catalyst component of the present invention is prepolymerized by a special method to change the composition and structure of the active center, thereby overcoming the problem of insufficient hydrogen sensitivity of the existing catalyst using the compound represented by formula (I) as an internal electron donor, and can further improve the hydrogen sensitivity of the catalyst. At the same time, the polymer synthesized by the catalyst has a higher bulk density.

[0007] According to a first aspect of the present invention, the present invention provides a method for prepolymerization of a solid catalyst component, comprising:

[0008] (1) in the presence of an inert solvent, allowing a catalyst component A, an alkyl aluminum and an external electron donor compound to contact and react; the catalyst component A contains a titanium element, a magnesium element, a halogen and an internal electron donor compound;

[0009] The internal electron donor compound includes a compound represented by formula (I);

[0010]

[0011] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0012] R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0013] The magnesium element comes from a magnesium-containing carrier, and the magnesium-containing carrier includes a magnesium compound represented by formula (II);

[0014]

[0015] In formula (II), R1 is a C1-C8 straight chain or branched chain alkyl group, or a C3-C8 cycloalkyl group;

[0016] R2 and R3 are the same or different, and are independently hydrogen or a C1-C5 straight or branched alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2;

[0017] (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction;

[0018] (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

[0019] Optionally, the mass ratio of the α-olefin to the catalyst component A is 0.04:1 to 10:1, and the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa.

[0020] According to the second aspect of the present invention, the present invention provides a solid catalyst component prepared by the prepolymerization method described in the first aspect of the present invention. The solid catalyst component comprises magnesium, titanium, halogen, poly-α-olefin and an internal electron donor compound, wherein the internal electron donor compound comprises a compound represented by formula (I);

[0021]

[0022] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0023] R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0024] The magnesium element comes from a magnesium-containing carrier, and the magnesium-containing carrier includes a magnesium compound represented by formula (II);

[0025]

[0026] In formula (II), R1 is a C1-C8 straight chain or branched chain alkyl group, or a C3-C8 cycloalkyl group;

[0027] R2 and R3 are the same or different, and are independently hydrogen or a C1-C5 straight chain or branched alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2.

[0028] According to the third aspect of the present invention, the present invention provides a catalyst for olefin polymerization, the catalyst comprising the solid catalyst component according to the second aspect of the present invention, an alkyl aluminum and an optional external electron donor compound or a reaction product thereof.

[0029] According to a fourth aspect of the present invention, there is provided a method for olefin polymerization, the method comprising: subjecting olefin to a polymerization reaction in the presence of the catalyst for olefin polymerization.

[0030] The catalyst of the present invention adopts a specific magnesium-containing carrier, and after being prepolymerized by a special method, the hydrogen adjustment sensitivity of the catalyst can be improved. At the same time, the polymer synthesized by the catalyst has a higher bulk density and a wider molecular weight distribution of the product, which is beneficial to improving the processing performance of the product. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0032] According to a first aspect of the present invention, the present invention provides a method for prepolymerization of a solid catalyst component, comprising:

[0033] (1) in the presence of an inert solvent, a catalyst component A, an alkyl aluminum and an external electron donor compound are contacted and reacted; the catalyst component A comprises titanium element, magnesium element, a halogen and an internal electron donor compound; the internal electron donor compound comprises a compound represented by formula (I);

[0034]

[0035] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 wherein the R'1 and R'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl or aromatic hydrocarbon groups are optionally replaced by other atoms;

[0036] The magnesium element comes from a magnesium-containing carrier, and the magnesium-containing carrier includes a magnesium compound represented by formula (II);

[0037]

[0038] In formula (II), R1 is a C1-C8 straight chain or branched chain alkyl group, a C3-C8 cycloalkyl group; R2 and R3 are the same or different and are independently hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2;

[0039] (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction;

[0040] (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

[0041] The preparation method provided by the present invention further comprises: (4) removing unreacted hydrogen, and sequentially performing solid-liquid separation and drying treatment on the system obtained in step (3) to obtain the solid catalyst component. In some preferred embodiments, the solid-liquid separation comprises filtering to remove the liquid, and then washing with hexane 1 to 2 times, and the drying treatment comprises vacuum drying, and the drying conditions include: a temperature of 10 to 80°C, preferably 40 to 50°C, and a time of 30 to 60 minutes. In the present invention, the vacuum drying can be implemented by a conventional vacuum pump, and the present invention has no special requirements for it.

[0042] Optionally, the inert solvent is selected from at least one of kerosene, paraffin oil, vaseline oil, white oil, methyl silicone oil, ethyl silicone oil, methylethyl silicone oil, phenyl silicone oil and methylphenyl silicone oil.

[0043] Optionally, based on 1 mol of the magnesium compound represented by formula (II), the amount of the inert solvent used is 0.8 to 10 L, preferably 2 to 8 L.

[0044] Optionally, the α-olefin is selected from one or more of ethylene, propylene, butene, octene and isopentene, preferably propylene.

[0045] Optionally, the mass ratio of the α-olefin to the catalyst component A is 0.04: 1 to 10: 1. For example, the mass ratio of the α-olefin to the catalyst component A can be 0.04: 1, 0.05: 1, 0.08: 1, 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1 or a range thereof.

[0046] Optionally, in step (1), the contact reaction conditions include: temperature of 0 to 30° C., preferably 15 to 25° C.; time of 1 to 30 min, preferably 10 to 20 min.

[0047] Optionally, the conditions for the polymerization reaction in step (2) include: a temperature of 0 to 50° C., preferably 15 to 25° C.; and a time of 5 to 30 min, preferably 10 to 20 min.

[0048] Optionally, the reaction conditions in step (3) include: temperature of 0 to 50° C., preferably 15 to 25° C.; time of 5 to 30 min, preferably 10 to 20 min.

[0049] Optionally, the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01 to 1.0 MPa, preferably 0.1 to 0.5 MPa, and more preferably 0.2 to 0.3 MPa.

[0050] According to the preparation method provided by the present invention, wherein, in step (1), the alkyl aluminum and the external electron donor compound can be selected with reference to the existing olefin prepolymerization catalyst, and the present invention has no particular limitation on this. Generally, the alkyl aluminum can be selected from one or more of triethyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, tri-n-hexyl aluminum and diethyl aluminum monochloride. The external electron donor compound can be selected from one or more of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane and dicyclopentyldimethoxysilane.

[0051] Generally, the molar ratio of the alkyl aluminum, the external electron donor compound and the amount of the catalyst component A calculated as titanium element can be 1 to 50: 0.2 to 10: 1. For example, the molar ratio of the alkyl aluminum, the external electron donor compound and the amount of the catalyst component A calculated as titanium element can be 1: 0.2: 1, 5: 0.2: 1, 10: 0.2: 1, 15: 0.2: 1, 20: 0.2: 1, 30: 0.2: 1, 40: 0.2: 1, 50: 0.2: 1, 15: 0.3: 1, 15: 0.5: 1, 15: 1: 1, 15: 2: 1, 15: 3: 1, 15: 4: 1, 15: 5: 1, 15: 20: 1 or any range of values ​​of the alkyl aluminum and the external electron donor compound in the above ratios.

[0052] According to the preparation method provided by the present invention, in step (1), the inert solvent can be selected with reference to the prior art. Generally, the inert solvent can be selected from one or more of hexane, heptane and decane. The amount of the inert solvent added is such that the mass concentration of the catalyst component A in the inert solvent can be 5 to 50 g / L.

[0053] According to the preparation method provided by the present invention, hydrogen can be added in the form of pure hydrogen or a hydrogen mixture. Preferably, the hydrogen mixture consists of hydrogen and an inert gas, and more preferably, the inert gas is selected from at least one of nitrogen, helium, neon and argon. The present invention has no special requirements for the concentration of hydrogen in the hydrogen mixture, as long as the defined reaction pressure can be achieved.

[0054] According to the preparation method provided by the present invention, the catalyst component A can be prepared according to the conventional method of the main catalyst in the olefin polymerization catalyst in the art, and the present invention is not particularly limited to this. For example, it can be prepared by referring to the methods disclosed in patent applications WO2012034357A1, WO2012097680A1 and patents ZL03153152.0, ZL200410062291.3, ZL201310491641.7, ZL201310491393.6 and ZL201310491648.9.

[0055] Specifically, the catalyst component A may include a reaction product of titanium tetrachloride, a magnesium-containing support and an internal electron donor compound such as carboxylic acid ester, wherein the magnesium-containing support is a spherical magnesium compound support.

[0056] In the present invention, the average particle size of the magnesium-containing carrier is 5 to 150 μm, preferably 20 to 80 μm, and more preferably 30 to 60 μm.

[0057] According to the preparation method provided by the present invention, the vacuum drying conditions in the above operation include: temperature of 40-50°C and time of 30-60 min. In the present invention, the vacuum drying can be implemented by a conventional vacuum pump, and the present invention has no special requirements for it.

[0058] According to the second aspect of the present invention, the present invention provides a solid catalyst component for olefin polymerization prepared by the prepolymerization method of the first aspect of the present invention, comprising magnesium element, titanium element, halogen, poly-α-olefin and internal electron donor compound, wherein the internal electron donor compound comprises a compound represented by formula (I);

[0059]

[0060] In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0061] R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl;

[0062] Wherein, the R"'1 and R"'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen on the aromatic ring in the aryl, alkylaryl or aromatic hydrocarbon group is optionally replaced by other atoms;

[0063] The magnesium element comes from a magnesium-containing carrier, and the magnesium-containing carrier includes a magnesium compound represented by formula (II);

[0064]

[0065] In formula (II), R1 is a C1-C8 straight chain or branched chain alkyl group, or a C3-C8 cycloalkyl group;

[0066] R2 and R3 are the same or different, and are independently hydrogen or a C1-C5 straight chain or branched alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2.

[0067] Optionally, the poly-α-olefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene and polyisoprene, preferably polypropylene.

[0068] Optionally, based on the total weight of the solid catalyst component, the content of magnesium in the solid catalyst component is 1 to 18 weight %, the content of titanium is 0.1 to 3.5 weight %, the content of halogen is 2 to 65 weight %, the content of poly-α-olefin is 0.1 to 89 weight %, and the content of internal electron donor compound is 0.6 to 15 weight %.

[0069] In some embodiments, based on the total weight of the solid catalyst component, the solid catalyst component contains 0.1 to 89 weight % of poly-alpha-olefin, 0.1 to 3.5 weight % of titanium, 1 to 18 weight % of magnesium, 2 to 65 weight % of chlorine and 0.6 to 15 weight % of internal electron donor compound. Preferably, based on the total weight of the solid catalyst component, the content of the poly-alpha-olefin is 1 to 50 weight %, the content of the titanium is 0.5 to 2.5 weight %, the content of the magnesium is 1 to 16 weight %, the content of the chlorine is 2 to 55 weight %, and the content of the internal electron donor compound is 1 to 10 weight %.

[0070] In some embodiments, based on the total weight of the solid catalyst component, the content of the poly-α-olefin is 9.5 to 35 weight %, the content of the titanium element is 1.5 to 2.5 weight %, the content of the magnesium element is 11 to 16 weight %, the content of the chlorine element is 40 to 55 weight %, and the content of the internal electron donor compound is 8 to 10 weight %.

[0071] Optionally, the halogen in the present invention is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine.

[0072] Optionally, the solid catalyst component is spherical solid particles.

[0073] Optionally, the average particle size D of the solid catalyst component 50 The average particle size D of the solid catalyst component is 5 to 150 μm, preferably 20 to 80 μm. 50 The thickness may be 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 100 μm, 120 μm, 150 μm or a range consisting of these.

[0074] In the present invention, the average particle size D 50 The particle size was measured using Master Sizer 2000 laser particle size analyzer (manufactured by Malvern Instruments Ltd).

[0075] According to the solid catalyst component provided by the present invention, the titanium content can be measured according to the colorimetric method. Specifically, 0.2-0.5g of the sample is dissolved in 50mL 2N H2SO4, the upper floating matter is filtered, and the clear liquid is taken for colorimetry; 2N H2SO4 solution is used as a blank, the thickness of the cuvette is 1cm, and the absorbance E1 is measured at a wavelength of 410μm, and then 1 drop of 30% H2O2 is dripped, shaken, and the absorbance E2 is measured, and the titanium content Ti (%) is calculated according to the following formula:

[0076] Ti%=[(E2-E1)×100) / (K·L·W·100)]×100

[0077] Where: W is sample weight (g); L is cuvette thickness (cm); K is specific extinction coefficient; E1 is blank absorbance; E2 is sample absorbance.

[0078] The magnesium content can be measured according to the EDTA titration method. Specifically, take 0.2-0.5g of the sample in a 250mL conical flask, add 20-30mL 2N H2SO4 solution to dissolve, add 20mL triethanolamine (1+2) standard solution, adjust pH=10 with 20% NaOH solution, shake, add 10mL pH=10 buffer solution, add 6 drops of 30% H2O2 and 30-50mL distilled water, add a small amount of chrome black T indicator, shake well, and titrate with 0.02N EDTA solution until the color changes from purple to blue (purple light disappears) as the end point, and calculate the magnesium content Mg (%) according to the following formula:

[0079] Mg(%)=[(VE·NE×24.31) / (G·1000)]×100

[0080] In the formula: G is the sample mass (g); VE is the amount of EDTA consumed (mL); NE is the equivalent number of EDTA solution; 24.31 is the atomic weight of magnesium.

[0081] The chlorine content can be measured by silver nitrate titration. Specifically, weigh 0.04-0.1g of sample into a conical flask, add 20mL 2N H2SO4 solution, and let stand for 30 minutes; rinse with distilled water several times, add 20-30mL 0.1N AgNO3 solution, add 3mL 1:1HNO3 solution, and titrate the excess AgNO3 solution with 0.1N NH4CNS standard solution until the brick red color does not disappear for two seconds as the end point, and calculate the chlorine content Cl (%) according to the following formula:

[0082] Cl(%)=[(V1-V2×D)×N1×35.45 / G·1000)]×100

[0083] In the formula: V1—amount of AgNO3 solution (mL); V2—amount of NH4CNS solution consumed (mL); D—volume ratio of AgNO3 / NH4CNS solution; N1—equivalent concentration of AgNO3; G—mass of sample (g); 35.45—atomic weight of chlorine.

[0084] The test method for the poly-α-olefin content in the solid catalyst component is as follows: weigh a certain amount of sample (M1) and dissolve it in ethanol and dilute hydrochloric acid, dry the insoluble matter at 80°C under vacuum to obtain a solid (M2), take 0.2g of the solid to make a tablet, measure the poly-α-olefin content (C1) of the solid by infrared spectrometer, and calculate the mass percentage of the poly-α-olefin in the solid catalyst component according to the following formulas:

[0085] C A =M2×C1 / M1

[0086] C A is the mass percentage of polyα-olefin in the solid catalyst component, M1 and M2 are the mass (g) of the sample and the dry solid, respectively, and C1 is the mass percentage of polyα-olefin in the dry solid.

[0087] The test method for the content of the internal electron donor compound in the solid catalyst component is: dissolve the sample with ethyl acetate and hydrochloric acid solution (concentration 2 mol / L), extract the internal electron donor compound, and analyze its content using a conventional liquid chromatograph.

[0088] According to the solid catalyst component provided by the present invention, the solid catalyst component further contains alkyl aluminum and an external electron donor. The types and contents of the alkyl aluminum and the external electron donor can be selected with reference to existing olefin prepolymerization catalysts.

[0089] In addition, the solid catalyst component of the present invention may contain other components, such as an inert solvent, in addition to the above components.

[0090] According to the third aspect of the present invention, there is provided a catalyst for olefin polymerization, which comprises a solid catalyst component prepared by the prepolymerization method of the present invention, an alkyl aluminum and an optional external electron donor compound or a reaction product thereof.

[0091] According to the catalyst provided by the present invention, the alkyl aluminum, the external electron donor compound and their respective contents can be selected according to the prior art.

[0092] Generally, the alkylaluminum can be selected from one or more of triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum and diethylaluminum monochloride.

[0093] The ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the solid catalyst component calculated as titanium element may be 1 to 1000: 1. For example, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the solid catalyst component calculated as titanium element may be 1: 1, 2: 1, 5: 1, 10: 1, 20: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1 or a range thereof.

[0094] Generally, the external electron donor compound can be selected from at least one of cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane, cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane and tert-hexyltrimethoxysilane.

[0095] The ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the external electron donor compound calculated as silicon element is 2 to 1000: 1. For example, the ratio of the molar amount of the alkyl aluminum calculated as aluminum element to the molar amount of the external electron donor compound calculated as silicon element can be 2: 1, 5: 1, 10: 1, 20: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1 or a range thereof.

[0096] According to a fourth aspect of the present invention, the present invention provides a method for olefin polymerization, the method comprising: subjecting olefin to a polymerization reaction in the presence of the catalyst for olefin polymerization described in the third aspect of the present invention.

[0097] According to the method provided by the present invention, the general formula of the olefin is CH2=CHR, R is hydrogen, C1-C6 alkyl or C6-C 10 Preferably, the olefin is selected from one or more of ethylene, propylene, butene, pentene and hexene.

[0098] According to the method provided by the present invention, the conditions of the polymerization reaction can be conventionally selected in the art, for example, the reaction temperature is 0 to 150° C., preferably the reaction temperature is 60 to 90° C., and the reaction pressure is normal pressure or higher pressure.

[0099] The advantages of the technical solution of the present invention will be described in detail below through specific embodiments.

[0100] In the following examples and comparative examples,

[0101] The isotactic index of a polymer (polypropylene) refers to the mass percentage of the polymer that is insoluble in boiling n-heptane under specified conditions. It is determined by the heptane extraction method (6 hours of boiling heptane extraction), i.e., 2 g of a dry polymer sample is taken, placed in an extractor and extracted with boiling heptane for 6 hours, and then the residue is dried to constant weight. The ratio of the mass (g) of the obtained polymer to 2 is the isotactic index.

[0102] The polymer melt index is measured according to the method of ASTM D1238-99.

[0103] In the following embodiments, unless otherwise specified, the "vacuum" refers to the vacuum degree achieved by a conventional vacuum pump.

[0104] The following preparation example is used to illustrate the preparation method of catalyst component A.

[0105] Preparation Example 1

[0106] In a 2L reactor, add 40g (0.4mol) of magnesium chloride, 280mL (4.8mol) of ethanol, 5g of ethyl acetate, and 5g of PVP (polyvinylpyrrolidone) as surfactants, heat to 90°C with stirring, react at this temperature for 2 hours, then add 190mL (2.4mol) of epichlorohydrin, continue to react at this temperature at 90°C for half an hour, then filter press, wash the filter press product with toluene 8 times, and finally dry the product in vacuum to obtain a spherical catalyst carrier Z1 for olefin polymerization.

[0107] The average particle diameter (D50) of the olefin polymerization catalyst spherical carrier Z1 is 56 microns, and the particle size distribution ((D90-D10) / D50) is 1.0. The particle morphology of the olefin polymerization catalyst spherical carrier Z1 is relatively regular, the surface is smooth, and it is basically spherical. The particle size distribution is relatively concentrated, and there are basically no irregular particles.

[0108] According to GC-MS, elemental analysis and NMR characterization, the structural formula of Z1 is:

[0109]

[0110] In a 2.5L glass reaction bottle, add 500mL of titanium tetrachloride, cool to -20°C, add 40g of the olefin polymerization catalyst spherical carrier Z1 obtained in Preparation Example 1, and stir at -20°C for 30min. Then, slowly heat up to 110°C, add 7.5mL of diethyl 2,3-diisopropyl-2-cyanosuccinate during the heating process, maintain at 110°C for 30min, and filter out the liquid. Then, add titanium tetrachloride and wash twice, and finally wash three times with hexane, and dry to obtain olefin polymerization catalyst A-1.

[0111] Preparation Example 2

[0112] In a 2L reactor, add 40g (0.4mol) of magnesium chloride, 280mL (4.8mol) of ethanol, 5g of ethyl acetate, and 5g of PVP (polyvinylpyrrolidone) as surfactants, heat to 90°C with stirring, react at this temperature for 2 hours, then add 1.6mol of epichlorohydrin, continue to react at this temperature at 90°C for half an hour, then filter press, wash the filtered product with toluene 8 times, and finally dry the product in vacuum to obtain a spherical catalyst carrier Z2 for olefin polymerization.

[0113] The average particle diameter (D50) of the olefin polymerization catalyst spherical carrier Z2 is 50 microns, and the particle size distribution ((D90-D10) / D50) is 1.0. The particle morphology of the olefin polymerization catalyst spherical carrier Z2 is relatively regular, the surface is smooth, and it is basically spherical. The particle size distribution is relatively concentrated, and there are basically no irregular particles.

[0114] According to GC-MS, elemental analysis and NMR characterization, the structural formula of Z2 is:

[0115] In a 2.5L glass reaction bottle, add 500mL of titanium tetrachloride, cool to -20℃, and add 40g

[0116] The spherical carrier Z2 of the olefin polymerization catalyst obtained in Preparation Example 2 was added thereto and stirred at -20°C for 30 minutes. Then, the temperature was slowly raised to 110°C, 7.5 mL of diethyl 2,3-diisopropyl-2-cyanosuccinate was added during the heating process, and the liquid was filtered off after maintaining at 110°C for 30 minutes. Then, titanium tetrachloride was added to wash twice, and finally washed three times with hexane, and dried to obtain olefin polymerization catalyst A-2.

[0117] The following examples are used to illustrate the solid catalyst component and its preparation method and the method for olefin polymerization of the present invention.

[0118] Example 1

[0119] (1) Preparation of solid catalyst component

[0120] In a 5L autoclave, add 1.1L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-1, react at 22°C for 10 minutes; then add 10g propylene, react at 20°C for 10 minutes, and vent the unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 15°C for 10 minutes, and vent the unreacted hydrogen. After filtering off the liquid in the reaction product, dry it under vacuum (temperature 45°C, time 40min.) to obtain a solid catalyst component, recorded as E-1.

[0121] (2) Propylene polymerization A

[0122] In a 5L autoclave, 1.3mmol triethylaluminum, 0.05mmol cyclohexylmethyldimethoxysilane, 10mL hexane and 15mg solid catalyst component E-1 were added, and after 1.5NL of hydrogen was introduced, 2.0L liquid propylene was added; the temperature was raised to 70°C while stirring and polymerization reaction was carried out at 70°C for 1 hour; stirring was stopped, and unpolymerized propylene monomer was removed to obtain polypropylene, which was recorded as P-1A.

[0123] Propylene Polymerization B

[0124] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-1B.

[0125] Example 2

[0126] (1) Preparation of solid catalyst component

[0127] In a 5L autoclave, add 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-2, react at 15°C for 10 minutes; then add 12g propylene, react at 25°C for 10 minutes, and vent the unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 20°C for 10 minutes, and vent the unreacted hydrogen. After filtering out the liquid in the reaction product, dry it under vacuum to obtain a solid catalyst component, recorded as E-2.

[0128] (2) Propylene polymerization A

[0129] Polypropylene was obtained by polymerization according to the method of propylene polymerization A in Example 1, except that E-2 was used instead of E-1, and polypropylene was obtained, which was recorded as P-2A.

[0130] Propylene Polymerization B

[0131] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-2B.

[0132] Example 3

[0133] (1) Preparation of solid catalyst component

[0134] In a 5L autoclave, add 1.0L hexane, 15mmol triethylaluminum, 0.3mmol cyclohexylmethyldimethoxysilane and 20.0g catalyst component A-2, react at 15°C for 10 minutes; then add 12g ethylene, react at 30°C for 10 minutes, and vent unreacted propylene; replace the reactor with nitrogen, add hydrogen to the reaction pressure of 0.2MPa, react at 25°C for 10 minutes, and vent unreacted hydrogen. After filtering out the liquid in the reaction product, dry it under vacuum to obtain a solid catalyst component, recorded as E-3.

[0135] (2) Propylene polymerization A

[0136] Polypropylene was obtained by polymerization according to the method of propylene polymerization A in Example 1, except that E-3 was used instead of E-1, and the polypropylene was recorded as P-3A.

[0137] Propylene Polymerization B

[0138] Propylene polymerization was carried out according to the method of propylene polymerization A, except that 6.5 NL of hydrogen was added, which was recorded as P-3B.

[0139] Comparative Example 1

[0140] Propylene Polymerization A

[0141] The method of propylene polymerization A and B in Example 1 was followed, except that catalyst component A-1 was used instead of E-1 to obtain polypropylene, which was recorded as CP-1A and CP-1B.

[0142] Comparative Example 2

[0143] Propylene Polymerization A

[0144] The method of propylene polymerization A and B in Example 2 was followed, except that catalyst component A-2 was used instead of E-2 to obtain polypropylene, which was recorded as CP-2A and CP-2B.

[0145] Comparative Example 3

[0146] The method of Preparation Example 1 was followed, except that 2,4-pentanediol dibenzoate was used instead of diethyl 2,3-diisopropyl-2-cyanosuccinate, to obtain a catalyst component, which was recorded as 2A-1.

[0147] According to the method for preparing the catalyst in Example 1, a catalyst component was obtained and recorded as 2E-1.

[0148] The method of propylene polymerization A and B in Example 1 was followed, except that 2A-1 and 2E-1 were used instead of E-1, to obtain polypropylene, which were recorded as 2PA-1A and 2PA-1B, 2PE-1A and 2PE-1B.

[0149] Table 1 Propylene polymerization results

[0150]

[0151]

[0152] It can be seen that the solid catalyst component of the present invention is used for olefin polymerization, and compared with the existing prepolymerization catalyst technology, such as compared with the comparative example, the catalyst hydrogen adjustment sensitivity is significantly improved, and the bulk density of the propylene polymer is also significantly improved, and the molecular weight distribution is significantly broadened, which is more conducive to resin processing.

[0153] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0154] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A prepolymerization method for a solid catalyst component, characterized in that: include: (1) in the presence of an inert solvent, a catalyst component A, an alkyl aluminum and an external electron donor compound are contacted and reacted; the catalyst component A comprises titanium element, magnesium element, a halogen and an internal electron donor compound; the internal electron donor compound comprises a compound represented by formula (I); In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 wherein the R'1 and R'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl or aromatic hydrocarbon groups are optionally replaced by other atoms; The magnesium element comes from a magnesium-containing carrier, and the magnesium-containing carrier includes a magnesium compound represented by formula (II); In formula (II), R1 is a C1-C8 straight chain or branched chain alkyl group, a C3-C8 cycloalkyl group; R2 and R3 are the same or different and are independently hydrogen or a C1-C5 straight chain or branched chain alkyl group, wherein the hydrogen on the alkyl group may be optionally replaced by a halogen atom; X is a halogen, preferably chlorine or bromine; m is 0.1-1.9, n is 0.1-1.9, and m+n=2; (2) adding α-olefin to the reaction system obtained in step (1) to carry out polymerization reaction; (3) removing the unreacted α-olefin in step (2), and adding hydrogen to the reaction system obtained in step (2) to carry out reaction.

2. The prepolymerization method according to claim 1, characterized in that The average particle size of the magnesium-containing carrier is 5 to 150 μm, preferably 20 to 80 μm, and more preferably 30 to 60 μm.

3. The prepolymerization method according to claim 1 or 2, characterized in that The inert solvent is selected from at least one of kerosene, paraffin oil, vaseline oil, white oil, methyl silicone oil, ethyl silicone oil, methylethyl silicone oil, phenyl silicone oil and methylphenyl silicone oil; And / or, based on 1 mol of the magnesium compound represented by formula (II), the amount of the inert solvent used is 0.8 to 10 L, preferably 2 to 8 L.

4. The prepolymerization method according to any one of claims 1 to 3, characterized in that The α-olefin is selected from one or more of ethylene, propylene, butene, octene and isopentene; And / or, the mass ratio of the α-olefin to the catalyst component A is 0.04:1 to 10:

1.

5. The prepolymerization method according to any one of claims 1 to 4, characterized in that In step (1), the contact reaction conditions include: temperature of 0 to 30°C, preferably 15 to 25°C; time of 1 to 30 min, preferably 10 to 20 min; And / or, the conditions of the polymerization reaction in step (2) include: temperature of 0 to 50° C., preferably 15 to 25° C.; time of 5 to 30 min, preferably 10 to 20 min; And / or, the reaction conditions in step (3) include: temperature of 0 to 50°C, preferably 15 to 25°C; time of 5 to 30 min, preferably 10 to 20 min; And / or, the amount of hydrogen added is controlled to maintain the reaction pressure at 0.01-1.0 MPa, preferably 0.1-0.5 MPa, more preferably 0.2-0.3 MPa.

6. A solid catalyst component prepared by the prepolymerization method according to any one of claims 1 to 5.

7. The solid catalyst component according to claim 6, characterized in that It includes magnesium element, titanium element, halogen, poly-α-olefin and internal electron donor compound; the internal electron donor compound includes the compound represented by formula (I); In formula (I), R'1 and R'2 are the same or different and are independently H, C1-C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; R'3 and R'4 are the same or different and are independently C1 to C 14 Straight chain alkyl, C3~C 14 Branched alkyl, C3~C 10 Cycloalkyl, C6~C 10 Aryl, C7~C 10 Alkyl or C7~C 10 Aralkyl; Wherein, the R'1 and R'2 are optionally bonded to each other to form one or more condensed ring structures, and the hydrogen atoms on the aromatic rings of the aryl, alkylaryl or aromatic hydrocarbon groups are optionally replaced by other atoms.

8. The solid catalyst component according to claim 7, characterized in that The poly-α-olefin is selected from one or more of polyethylene, polypropylene, polybutene, polyoctene and polyisoprene; And / or, based on the total weight of the solid catalyst component, the solid catalyst component has a magnesium content of 1 to 18% by weight, a titanium content of 0.1 to 3.5% by weight, a halogen content of 2 to 65% by weight, a poly-α-olefin content of 0.1 to 89% by weight, and an internal electron donor compound content of 0.6 to 15% by weight; Preferably, based on the total weight of the solid catalyst component, the content of the poly-α-olefin in the solid catalyst component is 1 to 50 weight %, the content of the titanium element is 0.5 to 2.5 weight %, the content of the magnesium element is 1 to 16 weight %, the content of the halogen is 2 to 55 weight %, and the content of the internal electron donor compound is 1 to 10 weight %; Further preferably, based on the total weight of the solid catalyst component, the content of poly-α-olefin in the solid catalyst component is 9.5-35% by weight, the content of titanium is 1.5-2.5% by weight, the content of magnesium is 11-16% by weight, the content of halogen is 40-55% by weight, and the content of internal electron donor compound is 8-10% by weight; And / or, the solid catalyst component is spherical solid particles; and / or, the average particle size D of the solid catalyst component 50 It is 5 to 150 μm, preferably 20 to 80 μm.

9. A catalyst for olefin polymerization, characterized in that: The catalyst comprises a solid catalyst component, an alkyl aluminum and an optional external electron donor compound or a reaction product thereof; The solid catalyst component is selected from at least one of the solid catalyst components described in any one of claims 6 to 8 and the solid catalyst component obtained by the prepolymerization method described in any one of claims 1 to 5.

10. A method for olefin polymerization, characterized in that: The method comprises: subjecting olefin to polymerization reaction in the presence of the catalyst for olefin polymerization according to claim 9; Preferably, the general formula of the olefin is CH2=CHR, R is hydrogen, C1-C6 alkyl or C6-C 10 The aromatic group; Preferably, the polymerization reaction temperature is 0 to 150°C, preferably 60 to 90°C.

Citation Information

Patent Citations

  • A spherical carrier for olefin polymerization catalyst and preparation method thereof

    CN104558281B

  • A solid composition, its preparation method and application

    CN104558283B

  • Catalyst component used for olefin polymerization and preparation method thereof as well as catalyst used for olefin polymerization and application

    CN104558284A

  • Olefin polymerization catalyst support, preparation method, catalyst component for olefin polymerization, olefin polymerization catalyst and applications of olefin polymerization catalyst support, catalyst component for olefin polymerization and olefin polymerization catalyst

    CN107915795A

  • Globular catalyst component used for olefine polymerization and its catalyst

    CN1289542C